Manager's Style and Image. (Zien Journal of Social Sciences and Humanities, 2023)
This article examines different management methods and social conflicts. Sotsialnye conflicty yavlyayutsya neizbejnoy chastyu obshchestvennoy zizni i mogut voznikat iz-za lichchnykh prichin, such as racial, ethnic, political and economic differences. Conflict management plays an important role in supporting stability, harmony, and society. V state analyziruyutsya different management methods, including diplomatic, political, legal and social-economic approaches. Issledovanie pokazyvaet, chto vybor methoda upravleniya mojet imet znachitelnoe influence na character i dlitelnost sotsialnyx konfliktov. The article describes the effectiveness of any management method and ego performance and social conflicts. Nekotorye podkhody mogut sposobstvovat peaceful resolution of conflicts and sodeystvovat sotrudnichestvu and mutual understanding among different groups of society. Other methods may lead to increased tension and conflict.